Towards a poly-functional synthetic-antimalarial vaccine: Incorporating non-natural elements into artificially-made peptides for mimicking functional pathogen ligand structures representing new site-directed vaccine components (2013)
The molecular basis for obtaining novel anti-malarial vaccine candidates depends on a considered selection of antigenic peptides, mainly derived from Plasmodium antigens' non-polymorphic regions. Since such targeted-molecules are poorly immunogenic when tested as vaccine components, they usually have to be modified to overcome their immunological phenotype. Transition state theory, explaining how peptidases catalyse a given peptide bond breakage, thus led to reduced amide pseudopeptides being proposed as possible mimetics for a transition-state. Stabilising such high-energy molecular stages could become a strategy for inducing antibodies potentially harbouring catalytic properties. Hence, isostere-bond peptido-mimetics represented a rational choice as potential abzyme-inducers and site-directed designed reduced amide pseudopeptides for obtaining peptide-analogues from selected malarial high-binding motifs. This novel family of vaccine candidates has proved to be an efficient functional antibody-inducer, the latter acting as efficient blockers of Plasmodium infection of human and mouse RBCs. © 2013 Bentham Science Publishers.